A Survey on Business Policy Violation in Web Service Integration - Amirthayogam, G; Anbu Ananth, C (International Journal of Computer Sciences and Engineering, 2019)
Rapid changes in the business rules in the world of business have proved to be an ethical factor in the assessment of the business logic. The ever-changing business world and the competitive nature of the process have led to the business logic to be an invaluable property for enterprises. The Web Service is the rising innovation in the field of business forms where the services offered by the association are overseen through the system called Change Management Framework. This framework is helpful for an organization to develop itself by satisfying the client requirements in a self-governing way. Service integration plays a major role in service discovery where there is a need to concentrate on the changing business logics .This is an arduous and time-consuming task. So the current attention is to have an automatic system to investigate the Business logics and distribute the felicitous style to integrate them. This paper gives an overview of recent research efforts made for dynamic web service integration and the methodologies adopted to understand the business policies and the techniques for identifying the business policy violations.